Answer:
x = 1 ± [tex]\sqrt{5}[/tex]
Step-by-step explanation:
x(x - 2) = 4
Multiply x on the left side by foil.
[tex]x^{2}- 2x = 4[/tex]
Subtract 4 on both sides.
[tex]x^{2} -2x-4=0[/tex]
Now, the quadratic formula.
x = (-b ± [tex]\sqrt{b^{2} - 4ac }[/tex]) / 2a
Using the standard form equation.
Ax² + Bx + C = 0
(1)x² - 2x - 4 = 0
A = 1
B = -2
C = -4
x = (-(-2) ± [tex]\sqrt{(-2)^{2}-4(1)(-4) }[/tex]) / 2(1)
x = (2 ±[tex]\sqrt{4+16}[/tex] ) / 2
x = (2±[tex]\sqrt{20}[/tex])/2
x = (2±2[tex]\sqrt{5}[/tex])/2
x = 1 ± [tex]\sqrt{5}[/tex]